Approximate Controllability from the Exterior for a Nonlocal Sobolev–Galpern Type Equation - Zamorano-Aliaga, S (Pleiades journals, 2021)
Abstract: In this paper, we study the approximate control problem from the exterior of a nonlocal equation of Sobolev–Galpern type, specifically the Barenblatt–Zheltov–Kochina equation, involving the fractional Laplace operator of order $$s\in(0,1)$$. We prove that the system under consideration is approximate controllable at any time $$T>0$$. © 2021, Pleiades Publishing, Ltd.